LA TIRANÍA DE LOS MEDIOS DE COMUNICACIÓN: UN ANÁLISIS NECESARIO - Martin Cañas, Kattia (2023)
It`s has been made an analysis of the important role of the press, in informing in an efficient way to the audience. The example used is the ICE`s Combo and the role fulfilled by La Nacion journal then. The retrieved idea is that, if media don't determinate what must be think, at least they influence the themes in wich is possible to think, and how to perceive them or respond to them: without the due informative balance and equity.